A High Efficiency and Wideband Doherty Power Amplifier for 5G - Hünerli, Halil Volkan (My University, 2017)
In today’s wireless communications, mobile networks need high data rates and low power consumption. For this purpose, novel wideband and energy efficient power amplifiers should be designed. This thesis is concerned with this problem. Doherty Power Amplifiers (DPAs) are popular architectures for obtaining high average efficiency for a large range of output power levels. In this work, a DPA is designed using WIN Semiconductor’s 50μm GaAs pHEMT process and a monolithic microwave integrated circuit (MMIC) layout ready for tape-out fabrication in Ka-band is created. In this thesis, a power amplifier consisting of two stages; a DPA and a pre-amlifier for improved gain, is designed and simulated. Main and auxiliary cells of the DPA are fed through an unequal Wilkinson power splitter. The simulations show that peak power added efficiency (PAE) of 40% and gain > 15 dB is achieved for the 26.5-31.5 GHz band. The PAE levels of 26% at 6 dB back-off and 18% at 9 dB back off is achieved at the center frequency of 29 GHz. Output power is larger than 26 dBm for the defined band. These properties make this design a promising candidate for future 5G applications.
Keywords: Informations- och kommunikationsteknik; Hållbar utveckling; Elektroteknik och elektronik; Telekommunikation; Elektronik; Information & Communication Technology; Sustainable Development; Electrical Engineering, Electronic Engineering, Information Engineering; Telecommunications; Electronics